2021
DOI: 10.1111/jth.15184
|View full text |Cite
|
Sign up to set email alerts
|

DHA 12‐LOX‐derived oxylipins regulate platelet activation and thrombus formation through a PKA‐dependent signaling pathway

Abstract: Background The effects of docosahexaenoic acid (DHA) on cardiovascular disease are controversial and a mechanistic understanding of how this omega‐3 polyunsaturated fatty acid (ω‐3 PUFA) regulates platelet reactivity and the subsequent risk of a thrombotic event is warranted. In platelets, DHA is oxidized by 12‐lipoxygenase (12‐LOX) producing the oxidized lipids (oxylipins) 11‐HDHA and 14‐HDHA. We hypothesized that 12‐LOX DHA‐oxylipins may be involved in the beneficial effects observed in dietary supplemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Previous studies have shown the regulatory effects of 14(S)-HDoHE on murine platelets and human alveolar macrophages in vitro (43,44). PD1/PDX also possesses potent anti-inflammatory functions in regulating neutrophil activation in vitro (45,46) and ameliorates pulmonary inflammation and fibrosis in vivo (47,48).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown the regulatory effects of 14(S)-HDoHE on murine platelets and human alveolar macrophages in vitro (43,44). PD1/PDX also possesses potent anti-inflammatory functions in regulating neutrophil activation in vitro (45,46) and ameliorates pulmonary inflammation and fibrosis in vivo (47,48).…”
Section: Discussionmentioning
confidence: 98%
“…Similar to arachidonic acid, DHA can also inhibit saturated fatty acid-induced TLR4 activity and reactive oxygen species, thereby inhibiting inflammation [13]. Furthermore, DPA has been widely demonstrated to contribute to inhibition of platelet activation, anti-inflammatory effects, blood lipid improvement, and cardiovascular protective effects [14][15][16][17]. Conversely, prostaglandins, metabolites of arachidonic acid, have been widely proven to have proinflammatory effects [18].…”
Section: Metabolism Of Fatty Acidsmentioning
confidence: 99%
“…Blood concentration was enhanced in pathological conditions such as morbid obesity ( 63 ) or metabolic syndrome ( 61 ), whereas the local level of 14-HDoHE was usually reduced in inflammatory conditions such as in arthritis ( 64 ), periodontitis ( 65 ), or pulmonary inflammation ( 66 ). 14-HDoHE was shown to be involved in the resolution of inflammation, to participate in the immune response or the platelet activation in reducing thrombus formation ( 67 , 68 ). If the mechanism of action of 14-HDoHE still remains unclear, a cerebral increase in 14-HDoHE may be a good marker to prevent potent neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%